The Soul of Man under Socialism - Wilde, Oscar, 1854-1900 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Soul of Man under Socialism" by Oscar Wilde is an essay published in 1891. Wilde presents a libertarian socialist vision that challenges conventional charity and capitalism. He argues that poverty prevents people from realizing their true potential and that well-meaning altruism only prolongs suffering by addressing symptoms rather than causes. Wilde advocates for a socialist society that abolishes private property, freeing individuals from material concerns to pursue creative self-development and artistic expression. He envisions socialism as a path to true individualism, not authoritarian control. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Soul_of_Man_Under_Socialism
Release date is 1997-08-01
Transcribed from the 1909 Arthur L. Humphreys edition by David Price
Keywords: Socialism